Diverse roles of assembly factors revealed by structures of late nuclear pre-60S ribosomes - Wu, Shan; Tutuncuoglu, Beril; Yan, Kaige; Brown, Hailey; Zhang, Yixiao; Tan, Dan; Gamalinda, Michael; Yuan, Yi; Li, Zhifei; Jakovljevic, Jelena; Ma, Chengying; Lei, Jianlin; et al. (Nature (London), 2016)
The cryo-electron microscopy structures of yeast nucleoplasmic pre-60S ribosomal particles give insight into the function of multiple assembly factors in ribosome biogenesis. Dissecting ribosomal biogenesis in the nucleus The ribosome is one of the largest macromolecular complexes in the eukarotic cell and its biogenesis is a highly complex process, involving hundreds of assembly factors, including many GTPases, ATPases and kinases. To gain insight into the function of these factors, Ning Gao and colleagues used cryo-electron microscopy to characterize structures of several nuclear pre-60S particles. Their data localize more than twenty assembly factors, which are particularly concentrated in two regions. The series of structures outlines three remodelling events that occur to the particle before it is transported to the cytoplasm. Ribosome biogenesis is a highly complex process in eukaryotes, involving temporally and spatially regulated ribosomal protein (r-protein) binding and ribosomal RNA remodelling events in the nucleolus, nucleoplasm and cytoplasm 1 , 2 . Hundreds of assembly factors, organized into sequential functional groups 3 , 4 , facilitate and guide the maturation process into productive assembly branches in and across different cellular compartments. However, the precise mechanisms by which these assembly factors function are largely unknown. Here we use cryo-electron microscopy to characterize the structures of yeast nucleoplasmic pre-60S particles affinity-purified using the epitope-tagged assembly factor Nog2. Our data pinpoint the locations and determine the structures of over 20 assembly factors, which are enriched in two areas: an arc region extending from the central protuberance to the polypeptide tunnel exit, and the domain including the internal transcribed spacer 2 (ITS2) that separates 5.8S and 25S ribosomal RNAs. In particular, two regulatory GTPases, Nog2 and Nog1, act as hub proteins to interact with multiple, distant assembly factors and functional ribosomal RNA elements, manifesting their critical roles in structural remodelling checkpoints and nuclear export. Moreover, our snapshots of compositionally and structurally different pre-60S intermediates provide essential mechanistic details for three major remodelling events before nuclear export: rotation of the 5S ribonucleoprotein, construction of the active centre and ITS2 removal. The rich structural information in our structures provides a framework to dissect molecular roles of diverse assembly factors in eukaryotic ribosome assembly.